Measuring Head Circumference in Neonates Weighing Less Than 2500 Grams - Roshanali, Farzam; Abdollahifar, Mohammad Amin; Mastery Farahani, Reza; Nazarnejad, Mohammad Mahdi (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: Anthropometric measures are important research goals especially because of racial differences and also variation in measurement techniques. In this study, head circumference in neonates weighing less than 2500 grams in Emam-Hosein hospital in 2018 was assessed. Aim: The aim of this study was to Measuring Head Circumference in Neonates Weighing Less Than 2500 Grams. Methods: In this cross-sectional study, 200 neonates weighing less than 2500 grams in Emam-Hosein hospital in 2018 were enrolled. The head circumference in neonates was determined and also was compared according to gestational age, birth weight, and sex. Results: There were 53% males and 47% females. There were 85.5% preterm neonates. Birth weight was less than 2000 gram in 12.5%. Head circumference was low in 148 cases (74%). The head circumference was not differed by gestational age, birth weight, and sex (p > 0.05). Conclusion: Totally, it may be concluded that head circumference is normal only in ¼ of neonates weighing less than 2500 grams and it is not an optimal goal for growth pattern monitoring.